2015
DOI: 10.3109/08820538.2015.1009557
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Complications in Laparoscopic Surgery: Review of Existing Literature and Possible Prevention and Treatment

Abstract: During laparoscopic surgery, ocular complications are possible, sometimes leading to devastating visual losses, hardly susceptible to recovery, although rare. Principal ocular adverse events are represented by corneal abrasions and the perioperative visual loss (POVL). POVL onset is related to intraocular pressure elevations (particularly after patient positioning in Trendelenburg or prone decubitus, depending on the surgical procedure), anesthesiologic factors and patients' characteristics. In the light of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…Takođe zbog povećanja intraokularnog pritiska treba biti oprezan kod pacijenata sa glaukomom jer se može javiti postoperativno slepilo. 27 Kompartment sindrom donjih ekstremiteta: nastaje kod dugotrajnih operacija u ektremnom Trendeleburgovom položaju koju prate loša arterijska perfuzija, kompresija venskih sudova nogu i loša venska drenaža iz femoralnih vena zbog PP. Simptomi ovog retkog stanja su bol, rabdomioliza i akutna bubrežna insufi cijencija.…”
Section: Komplikacijeunclassified
“…Takođe zbog povećanja intraokularnog pritiska treba biti oprezan kod pacijenata sa glaukomom jer se može javiti postoperativno slepilo. 27 Kompartment sindrom donjih ekstremiteta: nastaje kod dugotrajnih operacija u ektremnom Trendeleburgovom položaju koju prate loša arterijska perfuzija, kompresija venskih sudova nogu i loša venska drenaža iz femoralnih vena zbog PP. Simptomi ovog retkog stanja su bol, rabdomioliza i akutna bubrežna insufi cijencija.…”
Section: Komplikacijeunclassified
“…25,[29][30][31][32][33][34] After only a few minutes in the prone position, IOP can increase significantly. 35 According to the American Academy of Ophthalmology, 36 normal IOP is 10 to 21 mm Hg. Intraocular pressures higher than 21 mm Hg pose a risk for glaucoma, detached retina, and postoperative vision loss.…”
Section: Introductionmentioning
confidence: 99%
“…11 Th e type of anesthesia, the patient's intraoperative posture, and its duration and the fl uids utilized during hysteroscopy may fl uctuate the IOP. 12 Sudden peaks of IOP may decrease ocular perfusion pressure which is calculated by the dif-ference between mean systemic arterial pressure and IOP, and that may aggravate several ocular diseases such as retinal ischemia and glaucoma. 13 Currently, non-invasive intraoperative IOP measurement is available by portable digital tonometer devices which do not require specially trained staff .…”
Section: Introductionmentioning
confidence: 99%
“…Th us, the signifi cant IOP increase in both groups can be explained by the intraoperative posture. It was suggested that elevating the head over the heart level may decrease the episcleral pressure, hence the IOP peaks can be prevented 12. Th e prolonged operational times eventually increase fl uid input.…”
mentioning
confidence: 99%